Research on filter selection method for broadband spectral imaging system based on ancient murals. Issue 6 (23rd November 2015) - Liang, Jinxing; Wan, Xiaoxia; Liu, Qiang; Li, Chan; Li, Junfeng
Abstract: Digitization of cultural heritage protection has received considerable attention in heritage studies and spectral imaging technology has been playing an important role in this research. This article aims to study the technique of selecting optimal filter set to obtain ancient murals spectral image with high spectral and colorimetric accuracy based on the broadband spectral imaging system. The 330 Dunhuang murals mineral pigment color patches and the GretagMacbeth ColorChecker (CC) as well as 27 pieces of optical filters chosen as samples were examined. For each piece of filter, the three‐channel image was captured by the spectral imaging system. Then, 351 groups of six‐channel digital count images were acquired by arbitrary combinations of two among the 27 three‐channel digital count images. The pseudo‐inverse, principal component analysis, and R ‐matrix methods were used to reconstruct the spectral reflectance from the six‐channel digital counts for each sample. Finally, this study identified the optimal filter set by evaluating the integrated error (TOTAL ERROR), which was calculated by normalizing the mean spectral root‐mean‐square error (RMS), mean spectral goodness‐of‐fit error (1‐GFC), and mean CIEDE2000 color difference (ΔE00 ) and by multiplying them together. After the optimal optic filter set was selected, it was applied to the Dunhuang murals spectral imaging and was evaluated. The results showed that the optimal optic filter set could result in promising improvement both in spectral and color accuracy when compared with the production camera. In addition, it can be used for the construction of Dunhuang murals spectral image database. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 585–595, 2016